Pengaruh Ekspor Dan Penanaman Modal Asing Terhadap Cadangan Devisa Indonesia - Rolanda, Pynka; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of exports and foreign direct investment (FDI) on Indonesia's foreign exchange reserves from 1994 to 2024. Foreign exchange reserves are an important indicator in assessing a country's economic resilience, especially in the face of global dynamics. The analysis method used is multiple linear regression with the help of EViews software. The results showed that simultaneously, export and FDI variables had a significant effect on Indonesia's foreign exchange reserves. However, partially, only FDI shows a positive and significant effect, while exports have a positive but insignificant effect. The Adjusted R-squared value of 83.28% indicates that the variation in foreign exchange reserves can be explained by these two variables, while the rest is influenced by other factors outside the model. These findings provide important implications for the formulation of economic policies, especially in maintaining the stability and growth of foreign exchange reserves through optimizing the export sector and foreign investment flows.